2006
DOI: 10.1002/ana.20906
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone emissions and human brain excitability

Abstract: These results demonstrate that GSM-EMFs modify brain excitability. Possible implications and applications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 81 publications
5
64
1
1
Order By: Relevance
“…However, on the basis of earlier reported data, it has been shown that intracortical excitability of the motor cortex was modified by acute exposure to GSM 900 (Ferreri et al 2006). Intracortical inhibition/facilitation (ICI/ ICF) curves were investigated, and results showed that ICI is reduced and ICF is enhanced after exposure to GSM signal (Ferreri et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, on the basis of earlier reported data, it has been shown that intracortical excitability of the motor cortex was modified by acute exposure to GSM 900 (Ferreri et al 2006). Intracortical inhibition/facilitation (ICI/ ICF) curves were investigated, and results showed that ICI is reduced and ICF is enhanced after exposure to GSM signal (Ferreri et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, on the basis of earlier reported data, it has been shown that intracortical excitability of the motor cortex was modified by acute exposure to GSM 900 (Ferreri et al 2006). Intracortical inhibition/facilitation (ICI/ ICF) curves were investigated, and results showed that ICI is reduced and ICF is enhanced after exposure to GSM signal (Ferreri et al 2006). It has been suggested that ICI is mediated by GABA-A receptors (Hanajima et al 1998), ICF is mediated by glutamatergic N-methyl-D-aspartate (NMDA) (Ziemann et al 1998), and an imbalance between ICI and ICF may lead to changes in the intracortical excitability (Sanger et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, most studies have shown an influence of RF-EMFs on waking electroencephalogram, particularly on alpha rhythm (Croft et al, 2002(Croft et al, , 2008Curcio et al, 2005), as well as on sleep electroencephalogram, in which RF-EMFs influenced the alpha-sigma range (Huber et al, 2002;Regel et al, 2007). Significant effects on cerebral excitability have also been reported, with a localized, transient, and reversible increase of responsiveness of motor cortex as a function of GSM (Global System for Mobile Communications) exposure (Ferreri et al, 2006). Moreover, improvements on attentional performance have been reported as a consequence of GSM irradiation (Koivisto et al, 2000;Curcio et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ferreri et al studied the mobile phone emissions and human brain excitability [3] and Keetley et al studied the neuropsychological squeal of digital mobile phone exposure in humans [4], while Lin discussed the cataracts and personal communication radiation [5]. The effects of electromagnetic radiation of mobile phones on the central nervous system have been studied by Hossmann and Hermann [6] and the thermal effects of radiation from cellular telephones have been studied by Wainwright [7].…”
Section: Introductionmentioning
confidence: 99%